Opportunities for the Market Orientation Concept in the Healthcare Service: The Case of Hungary - Golesorkhi, Kia; Fojtik, János (Marketing & Menedzsment, 2019)
Market orientation (MO) in the healthcare service has always been subject of extensive debate. This paper is an attempt to expand this issue. For this purpose, we deliver a contrastive analysis on the MO and healthcare context. The paper concludes that: (a) Considering the new socio-economic contexts, MO can be perceived as an appropriate and applicable model for the healthcare service (b) Based on the wider definitions of the term customer (namely the internal customer concept), it is ethically appropriate to term patients customers of healthcare service as well (c) The main challenge of the implementation and institutionalization of MO in the healthcare environment remains to be the method to deal with the perception gaps between the stakeholders of healthcare on their own as well as each others’ roles before, during and after their meeting.